2020
DOI: 10.1177/1077558720935733
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Black and White: Mapping Misclassification of Medicare Beneficiaries Race and Ethnicity

Abstract: The Centers for Medicare and Medicaid Services administrative data contains two variables that are used for research and evaluation of health disparities: the enrollment database (EDB) beneficiary race code and the Research Triangle Institute (RTI) race code. The objective of this article is to examine state-level variation in racial/ethnic misclassification of EDB and RTI race codes compared with self-reported data collected during home health care. The study population included 4,231,370 Medicare be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…Four of these studies also found that Asian patients were more likely to be missing information identifying their race than white patients. 24 , 30 , 33 , 36…”
Section: Resultsmentioning
confidence: 99%
“…Four of these studies also found that Asian patients were more likely to be missing information identifying their race than white patients. 24 , 30 , 33 , 36…”
Section: Resultsmentioning
confidence: 99%
“…Race was determined by EHR demographic documentation. Racial misclassification is a particular problem for many NA studies that rely on administrative data, [27][28][29] and our data may not have identified all NA COPD patients. The diagnosis of COPD exacerbation in this study was based on physician documentation and coding.…”
Section: Discussionmentioning
confidence: 88%
“…Individual-level characteristics including age, sex, race/ethnicity, insurance, comorbidities, hospital length of stay, and use of home health care during the 120 days prior to the index hospitalization were extracted from the Medicare Beneficiary Summary File (MBSF) and OASIS files [ 18 ]. To minimize the frequency of unknown/other race and misclassification error, the imputed Research Triangle Institute (RTI) race variable contained in the Medicare Beneficiary Summary File (MBSF) was augmented with the patient’s self-reported race/ethnicity from the home health care assessment (OASIS) data [ 25 , 26 ]. We used six mutually exclusive racial/ethnic categories: non-Hispanic White, Black, Hispanic, Asian American/Pacific Islander (AAPI), American Indian/Alaska Native (AIAN), and unknown/other.…”
Section: Methodsmentioning
confidence: 99%